2010
DOI: 10.1055/s-0039-1697814
|View full text |Cite
|
Sign up to set email alerts
|

Garlic Burn in a Patient with Trigeminal Neuralgia: A Case Report

Abstract: Garlic is an herb which has been used by many cultures for treating various health problems for centuries. Uncontrolled use of herbal remedies, known as alternative treatment methods, may lead to side effects and serious treatment complications. This study aimed to draw attention to complications related to alternative treatment methods and to review the literature in the light of this case.A female patient who had been treated for trigeminal neuralgia was admitted to our clinic complaining of severe pain on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 9 publications
0
26
1
1
Order By: Relevance
“…Garlic (Allium Sativum) is an ancient naturopathic remedy for a variety of illnesses in many cultures. Hippocrates used it to treat leprosy, intestinal disorders, and chest pain (1)(2)(3)(4). Dioscorides supposed that garlic is clearing the arteries (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Garlic (Allium Sativum) is an ancient naturopathic remedy for a variety of illnesses in many cultures. Hippocrates used it to treat leprosy, intestinal disorders, and chest pain (1)(2)(3)(4). Dioscorides supposed that garlic is clearing the arteries (1).…”
Section: Discussionmentioning
confidence: 99%
“…From Roman times until Worl War I garlic poultices are used for a larvacidal medicine (1). During World War II, garlic was used to prevent infections after it had run out of antibiotics, so garlic was called "Russian Penicillin" (1,2,4). It has been shown that garlic affects fibrinolytic activity, lower cholesterol, glucose, and blood pressure levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Similar to home remedies employed for general health problems, alternative methods are also employed for oral health problems, although there is no scientific support as to their diagnostic, therapeutic, or preventive capabilities. [8][9][10][11] Complementary and alternative medical techniques can be used for dental problems. 12 Acupuncture has been used in the management of selected dental problems for years, 13 and herbal products can be used for the treatment of periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Ginkgo has been used for herbal medicine in China for thousands of years. Today, the extract of Ginkgo leaves is also one of the 10 best‐selling herbs in the United States (Yilmaz et al 2010). The standardized preparation of Ginkgo leaves extract, EGb761, is used in the clinic to treat thrombosis, inflammation, cardiovascular and Alzheimer's disease (Oken et al 1998, Rodriguez et al 2007, Sasaki et al 2002).…”
Section: Introductionmentioning
confidence: 99%